Exporting Sweatshops? Evidence from Myanmar - Tanaka, Mari (The Review of Economics and Statistics, 2020)
This study investigates the impacts of exporting on working conditions in Myanmar by drawing on a new firm survey. For the identification, I use the rapid opening of Myanmar to trade alongside the firm's proximity to airports and products that have generated variations in access to foreign markets. The results show that exporting has significant positive impacts on working conditions regarding fire safety, health management, and freedom of negotiation; positive insignificant effects on wages; and negative insignificant effects on working hours. I also find that exporting positively affects firm size, management practices, and the likelihood of receiving a labor audit.